The Pathology Resident Wiki: A Valuable Resource for Residents to Use on Call. (6th July 2015) - Greenwood, Michael P.; Carson, Joslin M.; Talmon, Geoffrey A.
Situations encountered on-call often bring some of the most unique and educationally rich questions to a pathology resident's attention which can be difficult to incorporate into institutional memory. A searchable online site (wiki) provides an easily accessible platform by which to do this and could serve as a valuable after-hour resident resource. Therefore, we evaluated a wiki's usefulness by creating a wiki using Campuspack for residents to catalog uncommon questions/situations encountered on call or rotations. After 41 months in use, analytic software embedded in the site was queried for usage statistics and one year's cohort of residents was surveyed to assess the wiki's value. Since the sites inception, over 7200 individual interactions with the site were recorded, with June through August being the most active period each year. Of the 15 residents surveyed, 60% utilized the site to answer a clinical question at least monthly and the majority (93%) considered the wiki a valuable on call resource. These findings suggest that an on-call wiki is a convenient tool for capturing the unique situations that pathology residents encounter. The majority of residents find the site a valuable resource and utilize it to answer clinical questions.